Ultra‐Small Nano‐Assemblies as Tumor‐Targeted and Renal Clearable Theranostic Agent for Photodynamic Therapy - Zhang, Dongsheng; Teng, Kun‐Xu; Zhao, Luyang; Niu, Li‐Ya; Yang, Qing‐Zheng (Advanced materials (Weinheim), 2023)
It is a challenge to design photosensitizers to balance between the tumor‐targeting enrichment for precise treatment and efficient clearance within a reasonable timescale for reducing side effects. Herein, an ultra‐small nano‐photosensitizer 1a with excellent tumor‐specific accumulation and renal clearance is reported. It is formed from the self‐assembly of compound 1 bearing three triethylene glycol (TEG) arms and two pyridinium groups in water. The positively charged surface with neutral TEG coating enables 1a to efficiently target the tumor, with the signal‐to‐background ratio reaching as high as 11.5 after tail intravenous injection. The ultra‐small size of 1a with an average diameter of 5.6 nm allows its fast clearance through kidney. Self‐assembly also endows 1a with an 18.2‐fold enhancement of reactive oxygygen species generation rate compared to compound 1 in organic solution. Nano‐PS 1a manifests an excellent photodynamic therapy efficacy on tumor‐bearing mouse models. This work provides a promising design strategy of photosensitizers with renal clearable and tumor‐targeting ability. Here, an ultra‐small nano photosensitizer is presented through a facile self‐assembly strategy that can target a disease state, boost reactive oxygen species (ROS) generation, as well as be cleared efficiently from the body in a reasonable amount of time.